Sport of Policy Analysis and Evaluation: a Systematic Literature Review - Muhlisin Muhlisin; Sandey Tantra Paramitha; Yudhi Purnama; Rif'iy Qomarullah; Muhammad Gilang Ramadhan (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2021)
The research is based on the lack of research and publications related to macro sports policy in Indonesia. Therefore, the purpose of this paper is to analyze research articles related to sports policy in Indonesia. This study uses a systematic literature review (SLR). The research population uses research articles related to sports policy and the research sample uses the purposive sampling technique using inclusive and exclusive criteria. The results of this study indicate that the direction of sports policy in Indonesia is still leading to achievement sports that focus on the development of the sport itself. It can be concluded that sport has not been able to become an important aspect in wider development (development through sport) and the results of the Literature Review, it can be concluded that the Evaluation Analysis of sports policy is still very minimal.